2022
DOI: 10.3390/en15103589
|View full text |Cite
|
Sign up to set email alerts
|

The 3E Optimal Location Assessment of Flat-Plate Solar Collectors for Domestic Applications in Iran

Abstract: The analytical hierarchy process (AHP) was utilized to determine the optimal location on which to install flat-plate solar thermal collectors for residential buildings in a number of cities in Iran under diverse climatic conditions. The payback period of investment (IPBP) was chosen as one of the decision criteria, while payback periods of energy and greenhouse gas emissions (EPBP and GGEPBP), being two recently introduced concepts, were also taken into account to provide a broader insight from the energy, eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Input data for all three scenarios regarding the prices of the PV technology are presented in Table 2. One of the most important social parameters, which is investigated by recent studies, is the number of newly created jobs related to the PV industry [45][46][47][48]. The implementation of PV systems in the Procida Municipality will create the need for new jobs, such as those related to the management, installation, and maintenance of these systems, as well as administrative tasks.…”
Section: Scenariomentioning
confidence: 99%
“…Input data for all three scenarios regarding the prices of the PV technology are presented in Table 2. One of the most important social parameters, which is investigated by recent studies, is the number of newly created jobs related to the PV industry [45][46][47][48]. The implementation of PV systems in the Procida Municipality will create the need for new jobs, such as those related to the management, installation, and maintenance of these systems, as well as administrative tasks.…”
Section: Scenariomentioning
confidence: 99%
“…With fossil fuels accounting for 97% of its energy mix, Iran's transition to renewable energy is critical for reducing greenhouse gases emissions [16,17]. Meanwhile, due to its advantageous geographic location, Iran has a wide range of renewable energy sources [18][19][20][21]. While the Iranian leadership recognizes climate change as an existential concern, combating it does not seem high on its priority list [22].…”
Section: Introductionmentioning
confidence: 99%
“…Jafari et al [18] explored an optimal location for installing domestic flat-plate solar thermal collectors in Iran based on the energy, economic, and environmental aspects. They applied an analytical hierarchy process and found that Yazd in the center of Iran was the best location to install the solar collector.…”
Section: Introductionmentioning
confidence: 99%